PERTANGGUNGJAWABAN PIDANA PELAKU MENGHIMPUN DANA DARI MASYARAKAT DALAM BENTUK SIMPANAN TANPA IZIN USAHA DARI PEMIMPIN BANK INDONESIA (Studi Putusan Nomor 2896/K/Pid.Sus/2022/PN Tng) - Br.Ginting, Vini Keysa Florentina Br.Ginting; July Esther; Herlina Manullang (Nommensen Journal of Legal Opinion, 2024)
The explanation of Article 16 of the Banking Law is that anyone who carries out activities to collect funds from the public is basically an activity that needs to be monitored. This is in line with the many establishments of banks or cooperatives that do not have official permits from Bank Indonesia. This is a criminal charge for the implementation of the scope of business licensing in Indonesia which in Article 46 paragraph (1) of the Banking Law has been explained. Such as the case of decision No. 2896/K/Pid.Sus/2022/PN Tng. This research uses normative juridical research methods. By qualitatively processing primary legal and secondary legal materials. The formulation of the problem that the author raises, namely What is the form of legal protection for victims that can be provided due to collecting funds in the form of deposits without permission according to positive law and What is the basis for judges' considerations in imposing criminal penalties against perpetrators who collect funds from the public in the form of deposits without a business license from the Chairman of Bank Indonesia. The results of the study concluded that the defendant's actions violated the provisions of positive law in Indonesia related to banking and business licensing in line with the judge's consideration to try and decide the defendant's sentence both in Juridical and Non-Juridical terms.